(untitled) (REVISTA DE AGRICULTURA NEOTROPICAL, 2023)
The hops (Humulus lupulus L.) has significant importance for Brazil since its consumption in the manufacture of beer is primordial, although the country imports almost 100% of the hops consumed. Research in this area has increased recently, bringing new information and guidelines to support national production and provide a technical basis for improving planting and cultivation techniques. The present study aimed to evaluate the influence of different light supplementations (Control - environmental condition, 400 µmol m-2 s-1, 600 µmol-2 m s-1, and 800 µmol m-2 s-1 ) on the production of hops seedlings in a greenhouse. We found that the responses are distinct among the cultivars used, but light supplementation increases variables related to physiological processes and seedling growth. Thus, we conclude that light supplementation with photosynthetically active radiation is advantageous for the production of hops seedlings since positive effects were found on the physiological characteristics of gas exchange related to photosynthesis and plant development when 400, 600, and 800 µmol m-2 s-1 were applied. In addition, the intrinsic responses of each cultivar should be observed to adapt the production system.